A relação escola e família durante o Ensino Remoto Emergencial na rede municipal da cidade de Uberlândia - Rezende, Jennyfer Deise Alves (2022)
The theme of our research is the relationship between school and family during Emergency Remote Teaching developed in the context of the COVID-19 pandemic. Our problem was constituted as follows: how was the relationship between school and family during Emergency Remote Teaching in the Municipal Network of Uberlândia during the years 2020-2021? We defined that the main objective of the research is to understand how the didactic materials prepared by professionals from the Secretary of Education of Uberlândia - SME express the relationship between school and family during remote teaching developed in the years 2020 and 2021, especially in the 1st year of Education Fundamental. This is qualitative research with a documentary approach. The documentary collection consisted of teaching materials – video lessons and respective PETs – produced and made available in the Escola em Casa program of the SME in Uberlândia for the 1st year of Elementary School. To support the analyses, we dialogued with authors who thought about the relationship between family and school in different times and spaces and the educational legislation in force in Brazil. (ARIÉS, 1973; MAGALDI, 2010; LIMA, 2002, among others) and the educational legislation in force in Brazil (Federal Constitution of 1988, ECA, LDB 9394/96). We also looked for the municipal regulations of the city of Uberlândia and federal regulations that regulated the ERE. We concluded that, during the ERE, the school granted the families the organization of the study routine, the creation of a suitable environment to study at home, and the monitoring of school activities carried out by the students. The analysis of the documents of this research allows us to infer that families were constantly called to responsibility, but as if they all had ideal conditions to make their homes a school. The expectation of monitoring activities, of help in organizing the routine, and even of physical adaptations of the space to achieve a suitable environment for studies, indicates that the guidelines seek to achieve an ideal family, which theoretically would have time and availability to accompany this child. and make the necessary changes.